1999
DOI: 10.1067/msy.2099.93791
|View full text |Cite
|
Sign up to set email alerts
|

The influence of clinical variables on hospital costs after orthotopic liver transplantation

Abstract: Length of stay is the most important determinant of costs after OLTx. Rational strategies to design cost-effective protocols after OLTx will require further studies to truly define the cost of various morbidities and outcomes after OLTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…This study clearly indicates the relation between intraoperative blood loss, surgical re-intervention during the in-hospital stay after liver transplantation, and a prolonged in-hospital stay. The requirement for additional operating procedures after liver transplantation is associated with high costs [24], and length of in-hospital stay has been shown to be the most important determinant of costs after liver transplantation [25]. As we found surgical re-intervention to be mainly related to more intraoperative blood loss and a prolonged inhospital stay, they were associated with higher costs.…”
Section: Discussionmentioning
confidence: 68%
“…This study clearly indicates the relation between intraoperative blood loss, surgical re-intervention during the in-hospital stay after liver transplantation, and a prolonged in-hospital stay. The requirement for additional operating procedures after liver transplantation is associated with high costs [24], and length of in-hospital stay has been shown to be the most important determinant of costs after liver transplantation [25]. As we found surgical re-intervention to be mainly related to more intraoperative blood loss and a prolonged inhospital stay, they were associated with higher costs.…”
Section: Discussionmentioning
confidence: 68%
“…10,11 We analyzed a cohort that traditionally incurs higher charges and uses more resources by using resource variables that account for most of the charges incurred during OLT. [12][13][14] Room and care charges, which are directly related to LOS, and treatments, including operating room charges and blood product use, account for up to two Our study using patients undergoing OLT at a single center eliminated other variations in clinical practices across transplant centers that may affect resource utilization, such as differences in surgical techniques, immunosuppression protocols, clinical expertise of transplant professionals, and immediate post-OLT management, as well as differences in severity of disease caused by regional differences in organ procurement and allocation. 14 Also, our sample was accrued over a relatively short period of 2 years, minimizing the role of improvements in peri-OLT management in results observed.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the costs related to retransplantation used in our analysis were the costs for an initial hepatic transplantation, yet several investigators have shown that hepatic retransplantation incurs costs that are significantly greater than for initial transplantation. [27][28][29] Specifically, Whiting et al 29 found in a recent analysis that the median cost of hepatic retransplantation is $97,000 more than initial OLT and is significantly correlated with increased cost on multivariate analysis. Markmann et al 27 found that longer hospital and intensive care unit stays for retransplantation patients contributed to a 170% increase in hospital charges for retransplantation patients.…”
Section: Discussionmentioning
confidence: 99%